DC Motor Rotary Speed Control with Arduino UNO Based PID Control - Rikwan, Rikwan; Ma'arif, Alfian (Peneliti Teknologi Teknik Indonesia, 2023)
Along with the development of the times, DC motors are often used in industrial equipment or household appliances, but in DC motors they often experience a decrease due to the given load, it requires a controller. This research uses PID (Proportional Derivative) controller. In this study, the DC motor can be controlled despite the load using the trial and error method. This study uses Arduino UNO software for testing using parameters Kp=1.5, Ki=0.87, Kd=0.27. parameter y is the parameter value Kp, Ki, Kd obtained from the system response according to the software used. the value of rise time = 0.9925 Tested, Time = 2.7368, Overshoot = 1.3333 and Steady State Error = 0